2022
DOI: 10.1007/s12288-022-01594-2
|View full text |Cite
|
Sign up to set email alerts
|

The Circular RNA Circ-ANAPC7 as a Biomarker for the Risk Stratification of Myelodysplastic Syndrome

Abstract: To assess the diagnostic value of circ-ANAPC7 expression levels in MDS and its risk stratification. This is a retrospective observational study. This study enrolled 125 patients diagnosed with MDS and divided them into five groups according to IPSS-R (very high group, 25; high group, 25; intermediate group, 25; low group, 25; and very low group, 25), and 25 patients with IDA were studied as control group from our bone marrow cell bank. Bone marrow cell were used as material in this study to measure the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Bioinformatics network analysis indicated that these three circRNAs are probably associated with multiple cancer-related molecular pathways, including Wnt/βcatenin and PTEN/Akt/mTOR [98,99]. Additionally, circ-ANAPC7 might be another promising circRNA biomarker, as its expression in MDS patients has recently been shown to be upregulated, along with the increasing risk group, by IPSS-R [100]. Finally, several circRNAs are differentially expressed between responders and nonresponders to azacytidine, although only one circRNA, hsa_circ_0006595, is considered a potential predictor for response to azacytidine treatment [101].…”
Section: Circular Rnasmentioning
confidence: 99%
“…Bioinformatics network analysis indicated that these three circRNAs are probably associated with multiple cancer-related molecular pathways, including Wnt/βcatenin and PTEN/Akt/mTOR [98,99]. Additionally, circ-ANAPC7 might be another promising circRNA biomarker, as its expression in MDS patients has recently been shown to be upregulated, along with the increasing risk group, by IPSS-R [100]. Finally, several circRNAs are differentially expressed between responders and nonresponders to azacytidine, although only one circRNA, hsa_circ_0006595, is considered a potential predictor for response to azacytidine treatment [101].…”
Section: Circular Rnasmentioning
confidence: 99%